Optical Properties Characterization of TiO₂-Metakaolin Composites Synthesized by the Sol-Gel Method - Berlian Sitorus; Felicia Silaban; Anthoni B. Aritonang (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Titanium dioxide (TiO2) is a semiconductor known for its excellent optical properties and is widely used in various applications. In this study, TiO2-Metakaolin composites were synthesized to investigate the optical properties of TiO2-Metakaolin in comparison to pure TiO2. The synthesis was conducted using the sol-gel method, with metakaolin concentrations varied at 0.5%, 1%, and 1.5% (w/v), based on the volume of the Ti(OH)n sol. XRF analysis revealed that the composite primarily consists of SiO2, TiO2, and Al2O3. XRD results confirmed that the synthesized TiO2 is in the anatase phase, while kaolin transformed from crystalline to amorphous metakaolin. FTIR analysis identified absorption peaks at wave numbers 3410–3448 cm-1 (OH), 2364–2357 cm-1 (OH), 1624–1633 cm-1 (Ti-OH), 1070–1072 cm-1 (Si-O-Si), 800–823 cm-1 (Ti-O), 547–555 cm-1 (Si-O or Al-O), and 464–480 cm-1 (Ti-O-Ti), indicating interactions between TiO2 and metakaolin. DRS-UV characterization showed that the band gap energies of the TiO2-metakaolin composites with metakaolin concentrations of 0.5%, 1%, and 1.5% (w/v) were 3.06 eV, 3.05 eV, and 3.11 eV, respectively. These values are lower than the band gap energy of pure TiO2 (3.18 eV), demonstrating that metakaolin effectively reduces the band gap energy of TiO2.